Environmental risk factors for the development of psoriatic arthritis: results from a case–control study - Pattison, E; Harrison, B J; Griffiths, C E M; Silman, A J; Bruce, I N (Annals of the rheumatic diseases, 2008)
Objective:To identify potential risk factors for the onset of inflammatory arthritis (IA) in a large cohort of patients with psoriatic arthritis (PsA) of recent onset.Methods:We recruited cases with psoriasis and an onset of IA within the past 5 years. Controls were patients who had psoriasis but no arthritis. We assessed potential factors associated with the development of IA using a detailed postal questionnaire. An unmatched analysis adjusted for age and gender was performed. Exposure was censored in the controls at a “dummy-date” assigned randomly in proportion to the percentage of cases developing IA in any given year.Results:We studied 98 cases and 163 controls. Exposures showing a positive association before the onset of IA in patients with psoriasis were: rubella vaccination (OR (95% CI) = 12.4 (1.2 to 122)), injury sufficient to require a medical consultation (2.53 (1.1 to 6.0)), recurrent oral ulcers (4.2 (2.0 to 9.0)) and moving house (2.3 (1.2 to 4.4)). Cases were also more likely to have experienced a fractured bone requiring hospital admission (50% vs 9%, p = 0.040).Conclusions:We found a number of environmental exposures associated with the onset of IA in subjects with psoriasis. The strongest associations were with trauma thereby adding to the hypothesis of a “deep Koebner phenomenon” in PsA. Our data also suggest that exposure of the immune system to certain infection-related triggers may also be of relevance. Further studies are needed to verify these observations and to examine potential immunological mechanisms that underlie them.